Inhibition of Soluble Epoxide Hydrolase for Renal Health - Liu, Jun-Yan (Frontiers in Pharmacology, 2019)
A soluble epoxide hydrolase (sEH) mediates the metabolism of epoxy fatty acids to form the respective vicinal diols, which are usually inactive or less active than the epoxide substrates. The sEH enzyme presents in many organs, including but not limited to the liver, heart, spleen, lung, and kidney. Here we summarized the changes in the expression and activity of sEH in multiple renal diseases, such as acute kidney injury (AKI), diabetic nephrology (DN), chronic kidney diseases (CKD), hypertension-mediated renal damage, and other renal dysfunctions. We also discussed the pharmacologic effects and the underlying mechanisms of sEH inhibition by using an inhibitor of sEH and/or the generic deletion of sEH on multiple renal diseases. We believe that sEH is a potential therapeutic target for renal dysfunction although the target disease needs further investigation.